Presence of classical music in generalist media: Case analisis - Sandulescu Budea, Alexandra María (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The following article analyses the presence and treatment of classical music in the Generalist Spanish press against the supplements of the same identifying spaces, genres and coverage through analysis sheet. The results present a minority presence of classical music compared to other musical genres in most of the headlines of the generalist media against a greater presence in supplements prioritizing opinion over information.